(untitled) (International Journal of Applied Sciences and Biotechnology, 2025)
Antibiotic resistance often incurs fitness costs that can impair bacterial growth, competitiveness, or adaptability in drug-free environments. However, these disadvantages are frequently offset by compensatory mutations, ecological interactions, and horizontal gene transfer, enabling resistant strains to persist and spread. This review explores the molecular basis and evolutionary dynamics of resistance-associated fitness costs, with a focus on how genetic, physiological, and environmental factors shape bacterial adaptation. We highlight experimental approaches to quantify fitness costs, the role of microbial communities and host environments, and emerging strategies to exploit evolutionary trade-offs. Integrating fitness cost insights into antibiotic stewardship and predictive modeling offers a promising path to managing resistance more effectively and prolonging the efficacy of existing therapies. Int. J. Appl. Sci. Biotechnol. Vol 13(2): 65-73.